2007
DOI: 10.2337/db06-1726
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulins Increase Mitochondrial Oxidative Capacity and Insulin Sensitivity in Skeletal Muscle Cells

Abstract: OBJECTIVE-Neuregulins are growth factors that are essential for myogenesis and regulate muscle metabolism. The addition of a recombinant neuregulin-1 isoform, heregulin-␤1 177-244 (Hrg), containing 3 nmol/l of the bioactive epidermal growth factor-like domain, to developing L6E9 myocytes has acute and chronic effects on glucose uptake and enhances myogenesis. Here, we studied the metabolic adaptation of myocytes to chronic treatments with Hrg. RESEARCH DESIGN AND METHODS-L6E9and C2C12 myocytes were chronically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 50 publications
(58 reference statements)
3
52
0
Order By: Relevance
“…PRC is the only family member induced at the RNA level following NRG plus IGF treatment but siRNA analysis indicated that this induction is not required. Schwann cells express both PGC-1- and PGC-1- and it is possible that either or both of these are involved, especially as the PGC-1 family are subject to multiple post-translational modifications and have been reported to be regulated by NRG (Canto et al, 2007;Lin et al, 2005). Alternatively, other transcriptional coactivators might be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRC is the only family member induced at the RNA level following NRG plus IGF treatment but siRNA analysis indicated that this induction is not required. Schwann cells express both PGC-1- and PGC-1- and it is possible that either or both of these are involved, especially as the PGC-1 family are subject to multiple post-translational modifications and have been reported to be regulated by NRG (Canto et al, 2007;Lin et al, 2005). Alternatively, other transcriptional coactivators might be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, other transcriptional coactivators might be involved. Other transcription factors might also be important: for example ERR has been shown to cooperate with NRF1 and NRF2 (Schreiber et al, 2004) and NRG has been shown to phosphorylate and induce NRF2-mediated mitochondrial gene expression (Canto et al, 2007;Fromm and Burden, 2001). Further studies will be required to dissect what is likely to be a highly regulated process.…”
Section: Discussionmentioning
confidence: 99%
“…In L6E9 muscle cells, NRG increases the expression of PGC-1␣ and PPAR␦, whereas PPAR␣ and -␥ are undetectable in these cultured cells despite the fact that skeletal muscle tissue expresses relatively high levels of PPAR␣. The NRG-dependent increase in mitochondrial activity is abrogated in a PPAR␦-dominant negative model but unaltered by PPAR␥ inhibition (9). PPAR␦ participates in muscle adaptation to training by increasing endurance capacity as a result of its effects on oxidative capacity, respiratory complex content, and PGC-1␣ expression (68,76).…”
Section: Is Neuregulin Involved In the Cellular Adaptations To Chronimentioning
confidence: 99%
“…Moreover, NRG increases the expression of multiple components of the insulin-signaling cascade in a PPAR␦-dependent manner (Fig. 3) (9). Given the similarities between the insulin and IGF-I signaling pathways, it would also be relevant to study whether NRG potentiates the IGF-I cascade.…”
Section: Is Neuregulin Involved In the Cellular Adaptations To Chronimentioning
confidence: 99%
“…Studies in quiescent adult rat ventricular cardiomyocytes show that NRG1 influences gene expression of multiple cellular systems, including factors involved in mitochondrial metabolism [9]. Additionally, in skeletal muscle, NRG1 treatment increased mitochondrial activity and membrane potential [37]. When assessing gene, expression using a panel focused on mitochondrial function we found that GGF2, when present by itself, did not dramatically alter expression of the studied mitochondrial related genes as seen in Figure 6.…”
Section: Discussionmentioning
confidence: 81%